(untitled) (Vallis Aurea, 2024)
Public health care institutions same as private health care institutions are present in almost every city in Croatia. Public health care institutions provide stability, security, and most of all they are traditionally among the people in Croatia. Private health care institutions are basically young and modern institutions with different and new management system. Main analyses and metrics which Policlinic Intermed uses in its business are SWOT analyses and BCG metrics. Through those methods and analyses this polyclinic can make right decisions in order to bring required marketing activities for this kind of business. A purpose of this research is to bring out strategies that are necessary for making marketing decisions and activities and clarify that private institutions are different then public ones and their need to be advertise and promote in order to survive on the market.